Molecular characterization of genotype XIIIb Newcastle disease virus from central India during 2006–2012: Evidence of its panzootic potential - Morla, Sudhir; Shah, Manisha; Kaore, Megha; Kurkure, Nitin Vasantrao; Kumar, Sachin (Microbial pathogenesis, 2016)
Newcastle disease virus (NDV) is the causative agent of Newcastle disease (ND) in many avian species. ND is a serious problem in developing countries, causing huge loss in the poultry industry. Although there are reports of continuous outbreaks of ND leading to serious losses to the poultry farming, very less is known about the genetic characteristics of its strains circulating in different parts of India. In the present study, we have five isolates of NDV reported from different outbreaks in Central India between the years 2006–2012. Deduced amino acid sequence of the F protein cleavage site and phylogenetic analysis of all the five isolates showed circulation of NDV genotype XIIIb. All the isolates showed a unique virulent cleavage site 112RRQKR↓F117. The close genetic similarity of all the isolates suggested circulation of the virulent NDV strains of the same ancestor in and around central India. Continuous isolation of genotype XIIIb NDV strains within the country suggests its panzootic potential. The study will be useful to understand the circulating strains of NDV and plan a vaccination strategy for poultry in India. •Newcastle disease virus (NDV) isolates from central India.•Pathotypic characterization of NDV isolates.•Genotypic characterization of NDV isolates.